Can non-conventional methods support recovery from exercise-induced muscle fatigue in people over 60 years old? - Rąglewska, Patrycja; Domaszewska, Katarzyna (Akademia Wychowania Fizycznego w Poznaniu)
Physical effort contributes to improving the level of physical fitness and fatigue tolerance, however, may cause overtraining and/or chronic fatigue. Recovery is a regenerative proces that takes place in every individual and is related to circadian rhythms. The aim of this review was to consider the factors and methods that determine and support the recovery from exerciseinduced muscle fatigue especially in older people above 60 years of age. We have searched three online databases: Web of Science, PubMed, and Google Scholar. Based on our narrative review, there are few non-conventional methods (like mindfulness and meditations) that play an important role among numerous nonpharmacological therapies used to enhance or maintain the cognitive function of the body and mind. However, there is still a gap concerning the inclusion of mindfulness meditation as a part of recovery from exercise-induced muscle fatigue.
Keywords: overtraining; recovery; meditations